Control Strategies for Scabies - Engelman, Daniel (Trop Med Infect Dis, 2018)
Scabies is a neglected tropical disease of the skin, causing severe itching and stigmatizing skin lesions. Further, scabies leads to impetigo, severe bacterial infections, and post-infectious complications. Around 200 million people are affected, particularly among disadvantaged populations living in crowded conditions in tropical areas. After almost 50 years, research into scabies control has shown great promise, particularly in highly-endemic island settings, but these findings have not been widely adopted. Newer approaches, utilizing ivermectin-based mass drug administration, appear feasible and highly effective. Inclusion of scabies in the WHO portfolio of neglected tropical diseases in 2017 may facilitate renewed opportunities and momentum toward global control. However, further operational research is needed to develop evidence-based strategies for control in a range of settings, and monitor their impact. Several enabling factors are required for successful implementation, including availability of affordable drug supply. Integration with existing health programs may provide a cost-effective approach to control.